2015
DOI: 10.1016/j.proeng.2015.07.329
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Stress State Characteristics on the Surface Fatigue Cracks Growth Rate Taking into Account Plastic Deformations

Abstract: The technique of fatigue tests of steel cross-shaped samples with a surface crack under biaxial loading is described. The sample and equipment for the implementation a biaxial tension and compression-tension in a working part of the sample are proposed. The sample and equipment for the implementation a biaxial tension and compression-tension in a working part of the sample are offered. Test results of structural steel 20 samples are presented. A stress effect parallel to a crack plane on its growth rate is det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
(19 reference statements)
0
3
0
4
Order By: Relevance
“…Gaur et al summarises the different effects observed for this type of loading condition. Some authors report a detrimental effect . Inversely, a certain number of authors report a beneficial effect .…”
Section: Consideration Of Biaxial Tension In Multiaxial Criteriamentioning
confidence: 99%
“…Gaur et al summarises the different effects observed for this type of loading condition. Some authors report a detrimental effect . Inversely, a certain number of authors report a beneficial effect .…”
Section: Consideration Of Biaxial Tension In Multiaxial Criteriamentioning
confidence: 99%
“…Для получения коэффициентов a и b для стали 09Г2С необходимо проведение экспериментальных исследований, поскольку объектом исследования является магистральный трубопровод. В частности, в работе [9] для стали 20 приведены следующие значения: а=3,25•10 -11 и b=3,0.…”
unclassified
“…К таким эффектам, в первую очередь, относятся остаточные напряжения, закрытие трещины, торможение скорости роста, взаимодействие изменяемых циклов нагружения [6,7]. В экспериментальных исследованиях [8,9] изучено взаимодействие постоянных и изменяющихся циклов нагружения на скорость роста усталостных трещин в стальных и никелевых образцах. В этих исследованиях изучалось явление закрытия трещин и было установлено, что упругая механика разрушения не позволяет моделировать эффекты, сопровождающиеся большими пластическими деформациями в вершине трещины.…”
unclassified
“…Результаты экспериментов. В статьях [9,10] исследована зависимость скорости роста усталостных трещин от вида напряженного состояния впереди фронта усталостной трещины, полученная при сравнении экспериментальных данных и данных вычислений, сделанных методом конечных элементов в упругопластической постановке задачи. Установлено, что скорость роста усталостных трещин зависит от размеров, формы и величины пластических деформаций в вершине трещины.…”
unclassified
See 1 more Smart Citation